A Composite Lymphoma Consisting of a Mantle Cell Lymphoma and a Peripheral T-Cell Lymphoma: A Rare Case With Literature Review. Issue 6 (November 2018) - Katsushima, Hiroki; Nakajima, Shinji; Takagawa, Masanori; Fukuhara, Noriko; Ichikawa, Satoshi; Itakura, Yuko; Harigae, Hideo; Ichinohasama, Ryo
Abstract : Abstract: A composite lymphoma (CL) is defined as 2 or more morphologically and immunophenotypically distinct lymphomas or lymphoid neoplasms that occur in the same organ or tissue. Many types of CL have been described in the literature, including 52 cases of CL with a component of mantle cell lymphoma (MCL) and only 2 cases of CL consisting of MCL and T-cell lymphoma. We hereby present a case of CL consisting of MCL and peripheral T-cell lymphoma, not otherwise specified. Morphologic features and flow cytometry analysis were both instrumental in the diagnosis of CL. In addition, we reviewed 52 reported cases of CL with MCL as a component. We found that the proliferation patterns of MCL have a relationship with the other component of the CL. We also found that many patients with CL had a history of lymphoproliferative disorders including lymphomas; this was observed in 9 of 52 cases, including 5 cases of MCL and 2 cases of another component of CL. This rate (approximately 17%) is relatively high and should not be ignored.